UTILIZATION OF THE FLOWER OF Tagetes Erecta LINN AS A REPELLENT AGAINST Aedes Aegypti L (DIPTERA: CULIDAE) MOSQUITO - Noviyanti, Ni Putu; Sudiarta, I Putu; Sri Sunari, Anak Agung Ayu Agung (International Journal of Biosciences and Biotechnology, 2022)
The use of Tagetes Erecta Linn flowers as a repellent against the Aedes Aegypti L mosquito (Diptera: culidae) has been carried out. Extraction of 570 grams of Tagetes flower samples was carried out by maceration using methanol to produce 44 grams of thick green extract. Phytochemical test results showed the methanol extract of Tagetes flower samples were positive for flavonoids. Compound fractionation was carried out and obtained 3 fractions, namely water fraction, acetone fraction and n-hexane. The results of the phytochemical test showed that the n-hexane fraction was negative for flavonoids, while the water and acetone fractions were positive for flavonoids. The total yield of flavonoids in the water and acetone fractions was 8293.2692 mg/100 grams and 4964.1148 mg/100 grams, respectively. The water fraction of Tagetes flower extract was tested for active compounds using the GC-MS instrument. Test the effectiveness of the repellent effectiveness of Tagetes flower compounds, the lowest was 5% at 5 hours at 9.35% and the highest was 20% at 1 hour at 60.58%.